FAKTOR-FAKTOR YANG MEMPENGARUHI AUDIT DELAY DAN TIMELINESS - Titik Aryati (Media Riset Akuntansi, Auditing & Informasi, 2005)
The purpose of the research is to find the influences of the firm size,the profitability, the existence of internal auditor division,and the public accountant size toward the audit delay and timelines.Fifty listed companies in Jakarta Stocks Exchange (JSX) were used as research sample. These listed companies were selected using (purposive) judgment sampling method. Analysis hypothesis using multiple regression, before hypothesis test, nor-mality data test using One Sample Kolmogorov-Smirnov Test.The result of regression model analyzing shows that audit delay is influenced by firm size. Also the result of regression model analyzing shows that timeliness is influenced firm size too.Keywords : audit delay,timeliness, firm size, profitability the existence of intemal au-ditor division, accountant public size